Patients with infectious diseases undergoing mechanical ventilation in the intensive care unit have better prognosis after receiving metagenomic next-generation sequencing assay. (September 2022) - Xi, Yin; Zhou, Jing; Lin, Zhimin; Liang, Weibo; Yang, Chun; Liu, Dongdong; Xu, Yonghao; Nong, Lingbo; Chen, Sibei; Yu, Yuheng; He, Weiqun; Zhang, Jie; et al.
Highlights: The relation between metagenomic next-generation sequencing (mNGS) and the prognosis of intensive care unit patients is not clear. mNGS assay is associated with a better prognosis in intensive care unit for infectious diseases. Absence of mNGS assay was an independent risk factor for increased mortality. mNGS can improve the range of pathogens detection. Abstract: Objectives: To evaluate the relation between metagenomic next-generation sequencing (mNGS) and the prognosis of patients with infectious diseases undergoing mechanical ventilation in the intensive care unit (ICU). Methods: This is a single-center observational study, comparing nonrandomly assigned diagnostic approaches. We analyzed the medical records of 228 patients with suspected infectious diseases undergoing mechanical ventilation in the ICU from March 2018 to May 2020. The concordance of pathogen results was also assessed for the results of mNGS, culture, and polymerase chain reaction assays. Results: The 28-day mortality of the patients in the mNGS group was lower after the baseline difference correction (19.23% (20/104) vs 29.03% (36/124), P  = 0.039). Subgroup analysis showed that mNGS assay was associated with improved 28-day mortality of patients who are not immunosuppressed (14.06% vs 29.82%, P  = 0.018). Not performing mNGS assay, higher acute physiology and chronic health evaluation II score, and hypertension are independent risk factors for 28-day mortality. The mNGS assay presented an advantage in pathogen positivity (69.8% double-positive and 25.0% mNGS-positive only), and the concordance between these two assays was 79.0%. Conclusion: mNGS survey may be associated with a better prognosis by reducing 28-day mortality of patients with infectious diseases on mechanical ventilation in the ICU. This technique presented an advantage in pathogen positivity over traditional methods.